Penerapan Kompetensi Kepribadian Guru dalam Interaksi Edukatif Menurut Ibnu Jama‘ah - Prayogi, Andro; Alfarisi Lingga, Salman; Rabumas, Rabumas; Nanda, Aria (Maslahah: Jurnal Pengabdian Masyarakat, 2020)
This activity aims to apply personality competence in educational interactions according to Ibn Jamaah. Teacher personality competence is the main provision in carrying out professional assignments. Some aspects of competence needed by teachers can improve morale and ethics in the world of education.The results of this activity teacher competencies in educational interactions according to Ibnu Jamaah set twenty-two points in essence Teacher Personality Competencies in interactions In addition, the relevance of Ibn Jama'ah thinking with contemporary education, which shows the suitability between teacher personality competencies in educational interactions according to Ibn Jama'ah with competence according to National Education Standards that have been set in accordance with the possession of mantab, stable, mature, wise, wise, be an example and have good character.Keywords: Personality Competence, Educative Interaction, Ibn Jama‘ah